About the concept and content of legal regulation of public procurement (International relations and international law Journal, 2018)
The article discloses the concept of public procurement, as well as the general characteristics of the fundamental international legal instruments in the field of regulation of public procurement. Legal regulation of public procurement is a complex and continuous process of acceptance, adjustment and using of state legal norms regulating public procurement through the establishment of common rules, rights and duties of its subjects. According to the authors, organization of procurement and its management are one of the main instruments of state influence on the economy of the country, which is aimed at obtaining the necessary quality and quantity of goods and services from a reliable supplier at a competitive price for the needs of the state. In this regard, the examples of legal regulation of public procurement in some foreign countries are given. However, the authors consider the relationship between the concepts of «public procurement» and «public order», regulation of public purchases within some international organizations and also by the legislation of the Republic of Kazakhstan. In conclusion, the authors note the significance of public procurement to ensure not only the implementation of target programs, but also the economic, legal, and social development of the state as a whole.Key words: state procurement, public procurement, government procurement, WTO, UNCITRAL.